2019
DOI: 10.1007/s13555-019-00345-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of the Efficacy of a Food Supplement in Increasing Photoprotection and Improving Selective Markers Related to Skin Photo-Ageing

Abstract: Introduction: Skin exposure to ultraviolet radiation (UVR) can cause oxidative stress, particularly in the absence of adequate protective measures or in individuals with a sensitive skin type. Most commonly, protection from UVR entails the use of topical sunscreens. Sunscreens, however, have various limitations. The objective of this study was to evaluate the efficacy and tolerability of an oral food supplement containing a combination of actives with mainly antioxidative properties (vitamins A, C, D3, E, sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 50 publications
1
47
0
Order By: Relevance
“…Radiance, moisture, elasticity and skin lightness were also significantly increased after supplementation. The authors concluded that this supplement improved photoprotection, enhanced the antioxidative status of the skin and improved general skin condition [44].…”
Section: In Vivo (Human)mentioning
confidence: 99%
“…Radiance, moisture, elasticity and skin lightness were also significantly increased after supplementation. The authors concluded that this supplement improved photoprotection, enhanced the antioxidative status of the skin and improved general skin condition [44].…”
Section: In Vivo (Human)mentioning
confidence: 99%
“…These effects were quantified in a later study by Kohli et al [12] where it was noted that the intensity of UVB-induced erythema decreased by an average of 8% post-PLE supplementation. Similarly, one study which did not utilize Fernblock®, noted increased MED among subjects with skin phototype I-III following once daily intake of an oral supplement containing PLE for 12 weeks [13] . The possible mechanism underlying PLE's anti-inflammatory properties include the inhibition of transcription factors and cytokines that mediate photoinflammation, namely, tumor necrosis factor (TNF), inducible nitric oxide synthase (iNOS), activator protein 1 (AP-1), and nuclear factor kappa B (NF-κB).…”
Section: Polypodium Leucotomos Extractmentioning
confidence: 99%
“…In a 12‐week open prospective single‐centre trial ( n = 30), the efficacy of a food supplement containing vitamins A, C, D3 and E, selenium, lycopene, lutein, green tea, polypodium and grape extracts upon MED was evaluated 10 . Significant improvement was found in MED levels, skin radiance and elasticity 10 …”
Section: Carotenoidsmentioning
confidence: 99%